Indigenous Bali Of Lontar Prasi Using Augmented Reality For Support Strengthen Local Cultural Content - Putu Wirayudi Aditama; I Gede Iwan Sudipa; Christina Purnama Yanti (Green Publisher Indonesia, 2022)
Lontar Prasi Bali is one of the cultural heritages that is still preserved in the Balinese life system. The problem is that the understanding of the Balinese Lontar Prasi can only be understood by some people so not all can understand the functions and stories contained in the Balinese Lontar Prasi. The solution to this problem is to provide a touch of Augmented Reality technology to show the story's contents in Lontar Prasi through 3D characters, audio, and text. The method used is the Prototyping Model chosen because it accommodates the scope and timeline of application development and facilitates communication between application developers and organizations. The test was conducted using four types of smartphones. The test results show that the four smartphones can be seen when the camera detects objects on the marker, Xiaomi Note 8 Pro and Oppo Reno F1 can detect objects within 1 second. While the Samsung A50s can detect objects for 2 seconds and the Xiaomi Redmi 5 can detect time for 3 seconds.